Alternative Means of Child Care Considerations from the Perspective of Article 20 of the Convention on the Rights of the Child of 1989 - Marta Prucnal-Wójcik (Jesuit University Ignatianum in Krakow, 2015)
Millions of children around the world are deprived of their family environment. All those children are a particularly vulnerable group and therefore there are entitled to special protection and assistance from the State. The basis for that protection have been incorporated into the provision of Article 20 of the Convention on the Rights of the Child of 1989 which requires from the States to ensure alternative care for such children. The aim of the article is to present the scope and content of Article 20 of the CRC. The author focuses on the interpretation of the most essential terms used in Article 20, such as "family environment" and "deprivation of child's family environment." She also analyses the nature and content of State's obligations towards a child living outside his or her family. The analysis of Article 20 is made from the legal perspective. Analyzed are the Travaux Préparatories of the article in question, Article 20 itself, The UN Guidelines for the Alternative Care of Children adopted in 2010, others provisions of the CRC and other relevant international documents and chosen subject literature.